Cannabinoids for the Treatment of Schizophrenia: An Overview - Capasso, Anna; Sobarzo-Sánchez, Eduardo; Fazel Nabavi, Seyed; Rastrelli, Luca (Current Topics in Medicinal Chemistry, 2016)
Cannabinoids are found to be very useful in psychiatry because of their antipsychotic properties suggesting a therapeutic use as neuroleptic agents in limiting psychotic diseases. Cannabinoids treatments are both able to reduce the typical symptoms of schizophrenia and to slow down the disease aggravation. In the present review, we reported recent studies supporting the idea that the cannabinoid system may modulate the activity of the striatum and temporal cortex linked to psychosis and schizophrenia. Furthermore, anatomical, electrophysiological, pharmacological and biochemical data suggest that the psychotic disorders related to the impaired cannabinoid system may lead to the development of novel compounds that selectively target specific elements of the cannabinoid system.
Keywords: Cannabis sativa